Comparative study on different annealing methods and choice of solvent in organic field effect transistors based on Poly(3-hexylthiophene) - Chua, C.L.; Woon, K.L. (De Gruyter Open, 2013)
A simple approach to study the effect of processing on the charge carrier mobility in an organic field effect transistor (OFET) based on regioregular poly(3-hexylthiophene) (RR P3HT) is investigated in this paper. It is found that different processing conditions can induce different degrees of hysteresis, which is well correlated with the charge mobility where lower hysteresis represents higher stability and hence higher charge mobility. Solvent annealing tends to create large nano-scale pinholes in P3HT which degrade the mobility.